ANALISIS BIAYA PELAKSANAAN PROYEK KONSTRUKSI Studi Kasus: Proyek Pembangunan Ruang Perpustakaan, Laboratorium Komputer, Ruang UKS, Rumah Dinas Kepala Sekolah, dan Penataan Halaman SD Negeri 5 Carangsari - Ida Bagus Gede Indramanik; Ni Kadek Astariani; I Wayan Sujarta (Fakultas Sains dan Teknologi Universitas Ngurah Rai, 2022)
The Library Room Development Project, Computer Laboratory, UKS Room, Headmaster's Office House, and Structuring of State Elementary School Page 5 Carangsari experienced delays in disbursement of the termin money from the time of its submission so that the contractor experienced a negative cash flow in a certain period in his efforts to complete the progress of his project. Therefore, it takes a method so that the contractor can estimate the cost of implementation by maximizing the completion of project progress using the ACWP (Actual Cost of Work Performed), BCWP (Budgeted Cost of Work Performed), and BCWS (Budgeted Cost of Work Shcedule) methods. The results of the analysis showed that the cost of ACWP was less with a profit of Rp. 320,927,690.00, bcwp and BCWS costs obtained the same result between expenditure and income (balanced). Overall at a cost of Rp. 1,057,744,110.00 contractors have been able to complete the project of Building Library Room, Computer Laboratory, UKS Room, Principal's Office House, and Structuring of State Elementary School Page 5 Carangsari with a contract value of Rp. 1,378,671,800.00.